Gender and Geographic Origin as Determinants of Manuscript Publication Outcomes: JBMR® Bibliometric Analysis from 2017 to 2019. (11th October 2022) - Rivadeneira, Fernando; Loder, Randall T.; McGuire, Anthony C.; Chitwood, Joseph R.; Duffy, Katie; Civitelli, Roberto; Kacena, Melissa A.; Westendorf, Jennifer J.
Abstract: The Journal of Bone and Mineral Research ( JBMR® ), the flagship journal of the American Society for Bone and Mineral Research (ASBMR), enjoys a premiere position in its field and has a global reach. The journal uses a single‐blind peer‐review process whereby three editors are typically involved in assessing each submission for publication, in addition to external reviewers. Although emphasizing fairness, rigor, and transparency, this process is not immune to the influence of unconscious biases. The gender and geographic diversity of JBMR® authors, editors, and reviewers has increased over the last three decades, but whether such diversity has affected peer‐review outcomes is unknown. We analyzed manuscript acceptance rates based on the gender and geographic origin of authors, reviewers, and Associate Editors. The analysis included 1662 original research articles submitted to JBMR® from September 2017 through December 2019. Gender was assigned using probabilities from an online tool and manually validated through internet searches. Predictor variables of manuscript outcome were determined with multivariate logistic regression analysis. The acceptance rate was highest when the first and last authors were of different genders, and lowest when both authors were men. Reviewer gender did not influence the outcome regardless of the genders of the first and last authors. Associate Editors from all geographical regions tended to select reviewers from their same region. The acceptance rate was highest when the Associate Editor was from Europe. Manuscripts with authors from North America and Australia/New Zealand had greater overall odds of acceptance than those from Europe and Asia. Manuscripts reviewed only by Editorial Board (EB) members had a lower acceptance rate than those refereed by non‐EB reviewers or a mix of EB and non‐EB reviewers. Overall, the geographical origin of authors, reviewers, and editors, as well as reviewers' EB membership may influence manuscript decisions. Yet, the JBMR® peer‐review process remains largely free from gender bias. © 2022 American Society for Bone and Mineral Research (ASBMR).